Assessment of outcome of patients admitted to 2 academic Emergency Departments with non-specific complaints (weakness) - Elahe Amirahmadi; Mehdi Rezaie; Fatemeh Meshkini; Mohammad Hosseinikasnavieh (Tehran University of Medical Sciences, 2022)
Background and aim: Having weakness and lethargy and feeling the need for hospital emergency services is one of the most important reasons for patients to go to hospital emergency rooms. The aim of the present study was to investigate the relationship between morbidity and mortality of patients with weakness and lethargy. Method: The present study was conducted in an observational and prospective manner in the emergency department of Rasool Akram and Firouzgar hospitals. The patients were divided into 5 groups by the evaluation team in the emergency triage unit using the international valid triage tool "Emergency Severity Index (ESI)". The patients were followed up for 2 months after the time of discharge and the patient's condition was examined in terms of illness, health or death. Result: Between levels 1 and 2 (patients with high severity conditions) and 3 (patient needs two or more emergency facilities in case of no disturbance in vital signs), level 3 had the highest frequency of referrals (61.9%). 90.7% had an underlying disease and 66.1% of the patients were taking medication at the time of visit. 11% of patients died in the first visit. In the initial follow-up, 23.7% of people were still sick, 40.7% had recovered and 17.8% had died. Conclusion: According to results in the final follow-up, 3.9% of people were still sick; the rate of recovered patients in the final follow-up was 44.1% and the percentage of deaths in the final follow-up was 24.6%. The high mortality rate indicates that the patients' concern was not due to weakness and lethargy, but due to a dangerous underlying disease that forced them to go to the hospital.